2020
DOI: 10.34172/jhp.2020.52
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking of a set of flavonoid compounds with Helicobacter pylori virulence factors CagA and VacA

Abstract: Introduction: Cytotoxin associated gene A (CagA) and Vacuolating cytotoxin (VacA) proteins are the main Helicobacter pylori (H. pylori) virulence factors. These toxins are associated with severe gastric diseases. Flavonoids are plant secondary metabolites that have shown great antibacterial effects. This work aimed to study the interaction of a set of flavonoid compounds with CagA and VacA proteins using molecular docking. Methods: A set of 54 flavonoid compounds were used in this study, and 36 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The molecular docking method was used to further analyze the receptor binding properties. The molecular docking method is commonly used for the research of ligand-protein interactions, prediction of binding affinities, and binding poses in drug development [63,64]. Autodock Vina [22] is a relatively new program for molecular docking combining Monte Carlo and gradient-based algorithms for the conformation search and a simple scoring function for interaction evaluations.…”
Section: Population Immunity and Vaccine Effectiveness As Factors Ass...mentioning
confidence: 99%
“…The molecular docking method was used to further analyze the receptor binding properties. The molecular docking method is commonly used for the research of ligand-protein interactions, prediction of binding affinities, and binding poses in drug development [63,64]. Autodock Vina [22] is a relatively new program for molecular docking combining Monte Carlo and gradient-based algorithms for the conformation search and a simple scoring function for interaction evaluations.…”
Section: Population Immunity and Vaccine Effectiveness As Factors Ass...mentioning
confidence: 99%
“…Flavones (5-hydroxyflavone) and flavonols (quercetin) have a high affinity for the potassium channel Kir6.1, acting on which some cardiovascular diseases can be treated [ 56 ]. Flavones (luteolin, apigenin) can serve as the basis of drugs that control the pathogenicity of Helicobacter pylori due to their ability to bind to one of the main virulence factors of bacteria of this species—vacuolating cytotoxin protein (VacA) [ 76 ]. Flavonols (quercetin), their glycosides (avicularin, hyperoside), and flavanonols (taxifolin) with comparable effects function as arginase inhibitors, which is a potential target for the development of new approaches to the treatment of leishmaniasis [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analyses of scoring functions calculated during molecular docking was studied in [ 54 , 56 , 71 , 73 , 76 , 77 , 78 , 79 ]. General information about the average affinities of each flavonoid group to the biological targets is presented in Table 3 and Table 4 for AutoDock and Glide software, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic arrangement and the presence of virulence factors dramatically determine the outcome of H. pylori infections. Previous studies showed that CagA and VacA factors are the most crucial virulence factors in H. pylori disease progression ( Jouimyi et al., 2020 ; Mubarakali et al., 2021 ); however, recent studies highlighted the importance of novel virulence factors including outer membrane vesicles (OMVs) ( Jarzab et al., 2020 ; Chew et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%